Understanding low-threshold mode-locking at multi-GHz repetition rate - Wenbin He; Meng Pang; Philip St. J. Russell (Light: Science & Applications)
Abstract Continuous-wave mode-locking at multi-GHz repetition rates is achieved in an ultrashort laser cavity at critical pulse energies 100 times lower than predicted by conventional theory. The authors reveal that dynamic gain depletion and recovery between consecutive round-trips is the key factor behind a low-pulse-energy transition from Q-switched mode-locking (QSML) to continuous-wave mode-locking (CWML). As well as providing new insight into gain dynamics, the results suggest a practical route to low-threshold lasing at very high-repetition rates.